The concept of 'IT artifact' has outlived its usefulness and should be retired now. (10th September 2014) - Alter, Steven
Abstract Vastly inconsistent definitions of the term "the IT artifact" in leading journals and conferences demonstrate why it no longer means anything in particular and should be retired from the active IS lexicon. Examples from the literature show why artifact‐cousins, such as the IS artifact, sociotechnical artifact, social artifact, and ensemble artifact should be used with great care, if not retired as well. Any void created by these retirements could be filled through the following approaches: (i) relabeling with simple terms that are immediately understandable; (ii) adopting guidelines for making sense of the whole X‐artifact family; and (iii) sidestepping the IT artifact and focusing directly on IT‐enabled work systems in organizations.